Analisis Sentimen Masyarakat Terhadap Direktorat Jenderal Pajak - Juli Supriyanto Gea; Haeni Budiati; Kristian Juri Damai Lase; Sunneng Sandino Berutu (Universitas Kristen Immanuel, 2024)
One process of recognizing opinions in the form of text to determine emotions neutrally, positively, or negatively is called sentiment analysis. Sentiment analysis will explore people's emotions from texts conveyed through various social media. Directorate general of taxes as data taken from twitter for analysis was used by the author to support research. Data collection is done by searching and collecting data with tax keywords from twitter, so that it can be analyzed to determine public sentiment. From the data collected and analyzed, 40.5% were neutral, 39.4% positive, and 20.1% negative.